2009
DOI: 10.1002/met.170
|View full text |Cite
|
Sign up to set email alerts
|

Index sensitivity analysis applied to the Canadian Forest Fire Weather Index and the McArthur Forest Fire Danger Index

Abstract: ABSTRACT:A number of different methodologies are developed for examining the sensitivities of an index. These methodologies are applied to examine the characteristics of the Canadian Fire Weather Index (FWI) and the McArthur Forest Fire Danger Index (FFDI) using 8 years of gridded data throughout Australia. Percentile changes in input conditions show that the indices are similar to each other in that they are both most sensitive to wind speed, then secondly to relative humidity and thirdly to temperature. On a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 7 publications
7
71
0
1
Order By: Relevance
“…As temperature goes up typically relative humidity goes down and this decreased humidity would further increase the drying rate and decrease equilibrium moisture levels, and thus lead to an overall increase in fuel drying. Indeed sensitivity studies on weather inputs and outputs of the FWI System have shown there to be strong influence of relative humidity (Dowdy et al 2010). We chose not to modify relative humidity in our temperature scenarios to provide a simpler albeit more conservative presentation of the amount of drying that might occur with increased temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…As temperature goes up typically relative humidity goes down and this decreased humidity would further increase the drying rate and decrease equilibrium moisture levels, and thus lead to an overall increase in fuel drying. Indeed sensitivity studies on weather inputs and outputs of the FWI System have shown there to be strong influence of relative humidity (Dowdy et al 2010). We chose not to modify relative humidity in our temperature scenarios to provide a simpler albeit more conservative presentation of the amount of drying that might occur with increased temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also note the role of wind speed in driving the elevated fire danger index values in the high-country in some instances, for example the event that occurred in the early morning of 29 November 2006. Fire danger indices are sensitive to changes in both wind speed and humidity and processes that cause large changes in both can have a significant effect on fire danger levels (Matthews 2008;Dowdy et al 2010;Bedia et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Which of the two should be used depends on the vegetation type (forest, shrub, grass). Here, FFDI or FGDI are adapted to the FWI according to Dowdy et al (2010). Time for ground attack and Air time are the time needed by ground and air suppression crews to reach the fire.…”
Section: Economic Losses To Housing By Bayesian Network Int J Wildmentioning
confidence: 99%